Beyond the Baby Blues: Maternal Factors Involved in Postpartum Depression - Prameswari, Yuda Nabella (UMBanjarmasin, 2025)
Postpartum depression (PPD) is a condition that can affect mothers after childbirth, leading to negative impacts on both mental and physical well-being. Although often considered an extension of the baby blues, PPD has more serious consequences and requires medical attention. This study aims to analyze maternal factors associated with the occurrence of postpartum depression in Banten Province. Using an observational analytic design with a cross-sectional approach and purposive sampling technique, the study involved 116 respondents. Data collection was conducted through the distribution of the Edinburgh Postnatal Depression Scale (EPDS) questionnaire. Data analysis using the Chi-square test revealed a significant association between parity and abortion history with the occurrence of postpartum depression (p < 0.001; OR 5.21; 95% CI 2.685-10.109 for parity, and p < 0.001; OR 3.92; 95% CI 1.788-8.596 for abortion history). However, no significant association was found between age, a history of depression, and spousal support with postpartum depression (p > 0.05). These findings underscore the importance of parity and abortion history as key factors in predicting the risk of PPD, which can be used to design targeted prevention and intervention programs for mothers in Banten Province. Keywords: Baby blues, Maternal, Perinatal Depression, Postpartum Depression